Youth Identity in Social Media (Virtual Ethnography Studies of Youth Identity Construction on “Kids Jaman Now” Content Youtube Channels) - S. N. Febriyanti; R. P. Tutiasri (Nusantara Science and Technology Proceedings)
Youth is the most unique stage of development, full of dynamics and full of problems throughout the human life span. At this time there were fundamental changes in various aspects, including biological, cognitive and social aspects (Steinberg, 1993). The impact of various changes, adolescents experience various shocks, both psychologically and socially. Based on this background, researchers are interested in conducting research on adolescent identity on social media, especially on the content of “Kids Jaman Now” which is viral on Youtube channels using Virtual Ethnographic studies. The approach used is qualitative. This approach assumes that reality is the result of mental construction of individuals. Researchers use virtual ethnographic methods. From the results of the Virtual Ethnographic Study and also the Focus Group Discussion conducted by researchers to see how the teenager's identity is constructed on “Kids Jaman Now” content on the youtube channel, it can be concluded that most of the content leads to negative identities including children and adolescents. This study aims to find the problems that occur on social media. The results of this study are expected to be a model of self-development learning in digital adolescence in order to eliminate the negative image of digital teenagers. In the next stage, it is expected that the learning model can be applied in the pilot project of learning self-development in adolescents in the digital era with the aim of forming teenagers who have a positive and ethical image of communicating through social media. So that the model can be applied to a wider segment of not only teenagers but also digital literacy for their parents so that there will be good dynamics in the process of mentoring in using gadgets and internet media.